(untitled) (Global Journal of Management and Business Research, 2020)
The bank liquidity phenomenon remains an unending theme of much debate among banking sector officials and the general banking public since it has the tenacity to derail economic activities in the event of chronic macro-economic fluctuations. Unstable macro economic environments are a formidable threat to bank liquidity positions as they play a significant role in deteriorating banks’ assets value which often diminishes banks’ liquidity. In the last two decades, the Zimbabwean economy has undergone periods of unstable economic conditions whose impact on the banking sector and especially on bank liquidity needs to be analysed so that appropriate intervention strategies can be designed to mitigate negative impacts in the event of recurrences. To analyse the liquidity positions of the country during these two decades of economic downturn, this research employed panel data stretching from 2010 to 2018 and panel regression models, to investigate the potential impact of macroeconomic changes on Zimbabwe’s bank liquidity.